2015
DOI: 10.1108/mip-02-2015-0039
|View full text |Cite
|
Sign up to set email alerts
|

Sailing the seven C ' s of blog marketing: understanding social media and business impact

Abstract: Purpose – Social media has transformed conventional marketing methods. This medium offers a unique blend of asynchronous communication, opportunities to co-create and customer empowerment far removed from traditional firm-to-consumer, push-vs-pull marketing messages. The purpose of this paper is to examine how a company developed long-term effective relationships and sales growth by using their blog to generate and enhance viral word-of-mouth message diffusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Implicit in gaining the trust of consumers in these settings is a rejection of unilateral company-centric brand management paradigms so that meaningful relationships can be facilitated through community access and engagement. The control of such access has, therefore, emerged as a key theme in the recent literature (Berthon et al 2012;Dobele, Steel & Cooper 2015;Fournier & Avery 2011;Gensler et al 2013), yet there is little agreement on what constitutes the optimal balance between flexibility and enforcement in relationship management within these environments.…”
Section: Obcsmentioning
confidence: 99%
“…Implicit in gaining the trust of consumers in these settings is a rejection of unilateral company-centric brand management paradigms so that meaningful relationships can be facilitated through community access and engagement. The control of such access has, therefore, emerged as a key theme in the recent literature (Berthon et al 2012;Dobele, Steel & Cooper 2015;Fournier & Avery 2011;Gensler et al 2013), yet there is little agreement on what constitutes the optimal balance between flexibility and enforcement in relationship management within these environments.…”
Section: Obcsmentioning
confidence: 99%
“…While most brands understand that blogs can be a way to enhance customer relationships and brand equity, they are at a loss of how to do so (Dobele et al , 2015). Compounding their lack of knowledge, brands have not evaluated the blog's performance to see where changes could be made to make the campaigns more effective (Liljander et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Twitter's use in industrial markets is a more recent phenomenon, with firms using Twitter to manage interactions with customers (Andzulis et al , 2012; Sashittal and Jassawalla, 2019). Twitter's conversational nature has prompted calls for research into the use of micro blogs in the aspect of innovation (Dobele et al , 2015). Simula et al (2013) found that firms involved in business markets displayed a level of hesitancy to adopt and utilise social media tools.…”
Section: Theoretical Frameworkmentioning
confidence: 99%